2018
DOI: 10.3390/app8101802
|View full text |Cite
|
Sign up to set email alerts
|

A Source Pollution Control Measure Based on Spatial-Temporal Distribution Characteristic of the Runoff Pollutants at Urban Pavement Sites

Abstract: The concentrations of pollutants in urban pavement runoff are normally higher than those in other urban surface runoff, which causes serious problems in protecting the environment of receiving water and soils. The purpose of this study was to propose a source pollution control measure based on the spatial-temporal distribution characteristics of the runoff pollutants at urban pavement sites. Therefore, samples from pavement runoff were collected and tested for analyzing the spatial-temporal distribution charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Although the results of the SEM and EDS suggest that phosphate precipitates are present on the surface of zeolite and limestone, the characteristic peaks for phosphate were not found by XRD. This indicates that the chemical interaction between the cations and the zeolites may have occurred mainly on the surface of the media [12]. It is also possible that the characteristic diffraction peaks of phosphate coincide with those of zeolite and limestone [30,48].…”
Section: Study On the Adsorption Mechanismmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the results of the SEM and EDS suggest that phosphate precipitates are present on the surface of zeolite and limestone, the characteristic peaks for phosphate were not found by XRD. This indicates that the chemical interaction between the cations and the zeolites may have occurred mainly on the surface of the media [12]. It is also possible that the characteristic diffraction peaks of phosphate coincide with those of zeolite and limestone [30,48].…”
Section: Study On the Adsorption Mechanismmentioning
confidence: 97%
“…Studies have shown that half of the nitrogen pollutants in urban rivers come from surface runoff formed during urban rainfall and the concentrations of metal elements in some runoff can exceed more than ten times the limitations for surface water quality [7,8]. Nitrogen, heavy metals, and phosphorus present in the surface runoff lead to the functional degradation of about two-thirds of urban rivers, and the pollutants discharged from this surface runoff present a serious threat to the urban water system [9][10][11][12]. In order to control the amount of nitrogen chemical oxygen demand (COD) and phosphorus in stormwater runoff and prevent the further deterioration of the urban water ecosystem, decentralized management of rainwater becomes critically important [13].…”
Section: Introductionmentioning
confidence: 99%
“…Y. Tian, B. Ma, K. Tian, N. Li, and X. Zhou determined the components of light screening preventive maintenance agent (LS pre-maintenance agent) for strong ultraviolet (UV) radiation areas and evaluated its performance [17]. C. Kou, A. Kang, P. Xiao, P. Mikhailenko, H. Baaj, L. Sun, and Z. Wu presented a source pollution control measure based on the spatial-temporal distribution characteristic of the runoff pollutants at urban pavement sites [10].…”
mentioning
confidence: 99%